A capacitance-coupled Ga2O3 memristor - Alfred Moore; Lijie Li; Hang Shao; Xiaoyan Tang; Huili Liang; Zengxia Mei; Yaonan Hou (AIP Advances)
Memristors are regarded as a key electronic component for non-von Neumann computing, such as neuromorphic networks. Hereby, we report a capacitance-coupled memristor (C-memristor) configured with ITO/Ga2O3/ITO coplanar interdigital structures. Depending on the voltage sweeping directions, the C-memristor exhibits a clear current switching with different polarities, offering an easy-to-readout electronic status. Due to the coupled capacitance, the difference between the currents in forward and reverse scanning strongly depends on the voltage sweeping speed, which was quantitatively studied with an equivalent circuit that we established. A device model based on filamentary conductive paths formed by the electrically driven oxygen vacancies was utilized to explain the working mechanism of the C-memristor, which aligns well with the observed results. Unlike previously reported Ga2O3 memristors that rely only on the status of the resistance, our device also exhibits capacitance variation, offering an additional degree of freedom (e.g., the power nodes) for constructing a neural network.